One Health in the consciousness of veterinary students from the perspective of knowledge of antibiotic therapy and antimicrobial resistance: a multi-centre study - Sobierajski, Tomasz; Wanke-Rytt, Monika; Chajecka-Wierzchowska, Wioleta; Śmiałek, Marcin; Hryniewicz, Waleria (Frontiers in Public Health, 2023)
One Health (OH) is one of the most essential global programs to rebalance the animal, human, and plant environments that depend on and affect each other. One element of the OH program is to draw attention to the phenomenon of antimicrobial resistance (AMR), which poses a very high risk to human and animal health. OH is not only a health-promoting project but also has an educational dimension. Therefore, a survey was conducted among 467 veterinary students studying at top academic centers in Poland to find out whether they had heard of OH and whether knowledge of OH influences their knowledge and attitudes related to AMR. The study indicated statistically significant relationships between familiarity with the OH program and the year of study. The higher the year of study, the more students heard about OH. It was also shown that students who had heard of OH were significantly more likely—compared to students who had not heard of OH—to agree that increasing AMR is influenced by the overuse of antibiotics in veterinary medicine (70.7 vs. 55%; p = 0.014) and the use of too low doses of antibiotics in animals (49.8 vs. 28.6%; p = 0.016). The higher the year of study, the higher the percentage of students who say that carbapenems as antibiotics of last resort should be reserved only for humans (70% of final-year students vs. 30.8% of first-year students; p < 0.001). The study's results indicate the effectiveness of education in fostering positive attitudes toward AMR and the impact of knowledge of the OH program on knowledge of antibiotic therapy in the spirit of OH.